Linfocitos T reguladores: Subpoblaciones, mecanismo de acción e importancia en el control de la autoinmunidad (2011)
Immune regulation is both an important mechanism for maintaining immune system homeostasis and for the establishment of tolerance towards self antigens in order to prevent the development of autoimmune diseases. It also plays an important role in maintaining peripheral tolerance by controlling a small population of circulating T cells, called regulatory T cells (Treg), which seems to have migrated from the thymus during relatively late stages1. The term “regulatory T cells” refers to cells that activate or suppress the function of other cells. Apparently, controlling the development of autoimmune diseases (For instance, lupus, thyroiditis, type I diabetes and inflammatory bowel disease among others), graft rejection and may play a critical role in asthma and allergy. © 2011 Asociación Colombiana de Reumatología